A Versatile Route To Cyclic (Alkyl)(Amino)Carbene‐Stabilized Stibinidenes. Issue 17 (22nd April 2022) - Philipp, Michael S. M.; Radius, Udo
Abstract: A convenient route for the synthesis of the cAAC Me (cAAC=cyclic (alkyl)(amino)carbene, cAAC Me =1‐(2, 6‐di‐ iso ‐propylphenyl)‐3, 3, 5, 5‐tetramethyl‐pyrrolidin‐2‐ylidene) and cAAC Cy (cAAC Cy =2‐azaspiro[4.5]dec‐2‐(2, 6‐diisopropylphenyl)‐3, 3‐dimethyl‐1‐ylidene) stabilized stibinidenes cAAC Me ⋅SbMes (2 a ) (Mes=2, 4, 6‐trimethylphenyl) and cAAC Cy ⋅SbMes (2 b ) is reported. A mechanism for the formation of [cAAC R Cl][SbCl3 Mes] 1 and cAAC R ⋅SbMes 2 from the reaction of cAAC with the antimony(III) precursor SbCl2 Mes, which proceeds via the isolable intermediate [cAAC R SbClMes][SbCl3 Mes] (3 ), is proposed. Abstract :